THE IMPACT OF SOCIAL MEDIA IMPLEMENTATION ON ADOLESCENT LANGUAGE DEVELOPMENT - Damanik, Bernieke Anggita Ristia; Banjarnahor, Stevani M (Cahaya Ilmu Bangsa Institute, 2025)
This research investigates the impact of social media usage on language development in adolescents. The study focuses on how frequent exposure to digital platforms affects vocabulary acquisition, language comprehension, and communication skills. It also examines the influence of online interactions on the development of informal and formal language styles among teenagers. Using a mixed-methods approach, including surveys and in-depth interviews, the findings highlight both the positive and negative effects of social media on language use. While social media fosters creativity and expands vocabulary through constant exposure to diverse content, it also presents challenges such as the informalization of language and potential negative impacts on grammar and writing skills. This research underscores the importance of balancing online interactions with real-world communication and parental guidance in shaping healthy language development in the digital age.